Effect of Selected Medicinal Plant Extracts on the Incidence of Pumkin Mosaic - Vimi Louis (Department of Plant Pathology, College of Horticulture, 1994)
The inhibitory effect of certain medicinal plant extracts on the incidence of pumpkin mosaic was studied using ten day old pumpkin seedlings as the test host. Preliminary screening of 30 species of medicinal plant extracts against pumpkin mosaic virus (PMV) revealed that eight plants possessed 80 or more percent inhibition of the infection. Of these five plants, namely, Basella alba, Glycyrrhiza glabra, Phyllanthus fraternus, Plumbago rosea and Thespesia populnea which showed very high virus inhibitory property were subjected to detailed studies. When the selected medicinal plant extracts were tested at five and ten per cent concentrations, two plants, B. alba and P. rosea showed more inhibition at lower concentration. P. fraternus and T. populnea were more effective at higher concentration. G. glabra showed equal effectiveness at both the concentrations. When the extracts of medicinal plants were mixed with partially purified virus preparation, B. alba, G. glabra and T. populnea showed more inhibition, than when used crude virus preparation. All the five medicinal plant extracts showed more inhibition by pre-inoculation application, than by post inoculation application. Pre – inoculation application of medicinal plant extracts at different time intervals revealed that inhibitory properties of B. alba and G. glabra decreased gradually, whereas, that of P. fraternus and T. populnea reached a maximum after a time gap. Inhibitory property of P. rosea did not show any gradual trend. Among the five selected medicinal plants, B. alba possessed a high degree of systemic effect (88.09%) followed by G. glabra (78.57%). The extracts of P. fraternus and P. rosea showed maximum reduction in percentage transmission of PMV by the vector (Aphis gossypii) when applied before acquisition and before inoculation feeding respectively. All the medicinal plant extracts showed more inhibition of infection in the case of mechanical transmission than in vector transmission. Spread of pumpkin mosaic in the field is not random and the data revealed that it is more or less concentrated around the initially infected plants.